Effects of Intra-Arterial Octreotide on Pancreatic Texture: A Randomized Controlled Trial. (September 2013) - Belyaev, O.; Polle, C.; Herzog, T.; Munding, J.; Chromik, A. M.; Meurer, K.; Tannapfel, A.; Bergmann, U.; Müller, C. A.; Uhl, W.
Background and Aims: Octreotide is suggested to harden the pancreas, thus facilitating the construction of a pancreatic anastomosis and lowering the risk of postoperative fistula. We tested the hypothesis that intra-arterial application of octreotide in the gastroduodenal artery during pancreatectomy may increase pancreatic hardness. Material and Methods: A single-center, prospective, double-blinded, randomized controlled trial with parallel assignment was conducted. Patients planned for a pancreatoduodenectomy or a total pancreatectomy, who had a palpatory and durometer proven (<40 Shore units) soft pancreas, were assigned to receive intraoperatively either 5 mL 500µg octreotide or 5 mL 0.9% saline solution as a bolus injection in the gastroduodenal artery. Pancreatic hardness was measured before, early, and late after intervention. The investigator performing the durometer measurements and pathologist were masked to group assignment. The primary outcome was increased pancreatic hardness. Analysis was by intention to treat. This trial is registered athttp://www.clinicaltrials.gov (ID NCT01400100). Results: A total of 12 patients received octreotide and 13 received saline solution. Pancreatic hardness marginally increased in the octreotide group: 0.67 ± 2.3 Shore units, whereas it decreased in the control group: −2.15 ± 2.7 Shore units. The difference was statistically significant, p = 0.029 (95% confidence interval = −4.87 to −0.77). Histology did not find any correlate for this clinically irrelevant hardening effect. Conclusions: A single bolus application of octreotide did not deliver a clinically relevant increase in pancreatic hardness. Future studies on the hardening effect of octreotide should employ repeated or continuous preoperative administration of this drug.